Impedance-based damage assessment of steel-ECC composite deck using piezoelectric transducers - Sun, Rui; Li, Yunjuan; Qin, Fengjiang; Zhang, Zhigang (Frontiers in Materials, 2022)
The excellent crack and fatigue resistance of Engineering Cementitious Composites (ECC) materials makes it promising to be used in orthotropic bridge deck system. However, overloading and fatigue load might cause structural damage and, consequently, structural performance degrada-tion. In this work, the piezoelectric lead-zirconate-titanate (PZT) transducers are used to identify the structural damage of the steel-ECC composite deck by implementing both experimental test and numerical simulation. Two steel-ECC composite deck are prepared and four-point bending loading tests are performed on the two specimens to introduce several damage scenarios by gradually increasing the load. The impedance output signals of the piezoelectric sensors are measured under different damage scenarios, and the damage index are extracted to identify the structural damage. A finite element model of the steel-ECC composite deck is established, and the impedance signals with different damage scenarios are calculated and used to assess the structur-al damages. According to the experimental test and numerical simulation, the impedance-based technology performs to be an effective way to identify the structural damage of the steel-ECC composite deck.